Crystallographically Determined Etching and Its Relevance to the Metal-Assisted Catalytic Etching (MACE) of Silicon Powders - Kolasinski, Kurt W.; Unger, Bret A.; Ernst, Alexis T.; Aindow, Mark (Frontiers in Chemistry, 2019)
Metal-assisted catalytic etching (MACE) using Ag nanoparticles as catalysts and H2O2 as oxidant has been performed on single-crystal Si wafers, single-crystal electronics grade Si powders and polycrystalline metallurgical grade Si powders. The temperature dependence of the etch kinetics has been measured over the range 5 – 37 °C. Etching is found to proceed preferentially in a <001> direction with an activation energy of ~0.4 eV on substrates with (001), (110) and (111) orientations. A quantitative model to explain the preference for etching in the <001> direction is developed and found to be consistent with the measured activation energies. Etching of metallurgical grade powders produces particles, the surfaces of which are covered primarily with porous silicon (por-Si) in the form of interconnected ridges. Silicon nanowires (SiNW) and bundles of SiNW can be harvested from these porous particles by ultrasonic agitation. Analysis of the forces acting between the metal nanoparticle catalyst and the Si particle demonstrates that strongly attractive electrostatic and van der Waals interactions ensure that the metal nanoparticles remain in intimate contact with the Si particles throughout the etch process. These attractive forces draw the catalyst toward the interior of the particle and explain why the powder particles are etched equivalently on all the exposed faces.